Impact of COVID19 on resident physicians of a community hospital in New York city - Binav Shrestha; Oday Alhafidh; Osama Mukhtar; Ramakanth Goel Pata; Nabin Kc; Muchi Ditah Chobufo; Vijay Gayam; Saroj Kandel; Shivani Thapa; Danilo Enriquez; Joseph Quist; Francis Marie Schmidt (Greater Baltimore Medical Center, 2021)
Introduction: Novel Corona Virus Disease 19 has created unforeseen burden on health care. New York city is one of the epicenters of pandemic and here we explore physical, mental and social impact of COVID 19 on Resident Physicians (RP) working within the center of this epicenter. Methods: This is a single-center cross-sectional web-based survey involving RP of a community hospital in Brooklyn, New York. Questionnaire was formulated in online platform. We used a convenient sampling method. Univariate analysis was conducted and presented the distribution of qualitative responses as frequency and percentages. Result: COVID19 related symptoms were reported by 39.8% RP. COVID19 IgG and IgM antibodies, both negative were reported by 34.9%, while only 6% RPs were IgG antibody positive. Symptomatic RP tested for COVID19-PCR was positive in 42.42%. Self-isolation from family during the pandemic was reported by only 14.5%. Financial constraints, lack of accommodation, and emotional reasons were main reasons of not being able to self isolate. Being bothered by 'Anxiety' and 'Nervousness' were reported by 8.5% on 'Almost every day' while 46.3% reported on 'several days in the two weeks duration'. 'Uncontrollable worrying', 'Feeling down', 'Depressed,' or 'Hopeless' was reported as 'Not at all' by 78.8% and 3.7% reported it to 'occur nearly every day for the last two weeks'. Conclusion: Aftermath of fight against pandemic has left RP with significant physical, mental, and social impact. Appropriate stress management and safety interventions are urgently needed. Further studies are needed to explore the detailed impact of COIV19 on RP.